Assessing the benefits of integrated introduced predator management for recovery of native predators. Issue 7 (21st June 2021) - Jessop, Tim S.; Holmes, Ben; Sendjojo, Arvel; Thorpe, Mary O.; Ritchie, Euan G.
Abstract : Increasingly threatened species and their habitats require multiple successful management actions to ensure persistence. Introduced predator exclusion and suppression programs are key conservation actions used to retain or restore Australian ecosystems. Nevertheless, few direct comparisons are made to ascertain the individual and combined efficacy of multiple introduced predator conservation actions to benefit biodiversity. When colocated, both management actions could generate additive conservation benefits that greatly assist the recovery or persistence of threatened native species. Varanid lizards are key functional components in Australian predator guilds and could benefit, via ecological release, when introduced predator management actions are successful. Here we tested the effects of a colocated predator‐exclusion fence and lethal fox baiting on varanid site occupancy in a semiarid protected area. Varanid site occupancy was higher at sites inside (Ψ = 0.90 ± 0.26) compared to sites outside (Ψ = 0.61 ± 0.28) the introduced predator‐proof fenced enclosure. There was only weak evidence of increased varanid site occupancy at fox baited sites (Ψ = 0.037 ± 0.024) compared to nonfox baited (Ψ = 0.00) sites. Overall, colocated introduced predator management actions achieved some additive benefits via possible spillover fencing effects for native mesopredator populations. However, most potential benefits to varanid populations outside of the predator‐proof fenced enclosure were absent due to unsuccessful lethal‐baiting effects on fox populations. The predator‐proof fenced enclosure nevertheless provides important habitat refugia for future source populations for reintroduction once adjacent protected areas become suitable.